A novel type of angle steel buckling-restrained brace Cyclic behavior and failure mechanism. - Zhao, Junxian (Earthquake engineering & structural dynamics.)
A novel type of angle steel buckling-restrained brace (ABRB) has been developed for easier control on initial geometric imperfection in the core, more design flexibility in the buckling restraining mechanism and easier assembly work. The steel core is composed of four angle steels to form a non-welded cruciform shape restrained by two external angle steels, which are welded longitudinally to form an external tube. Component test was conducted on seven ABRB specimens under uniaxial quasi-static cyclic loading. The test results reveal that the consistency between the actual and design behavior of ABRB can be well achieved without the effect of weld in the core. The ABRBs with proper details exhibited stable cyclic behavior and satisfactory cumulative plastic ductility capacity, so that they can serve as effective hysteretic dampers. However, compression-flexure failure at the steel core projection was found to be the primary failure mode for the ABRBs with hinge connections even though the cross section of the core projection was reinforced two times that of the yielding segment. The failure mechanism is further discussed by investigating the Nu-Mu correlation curve. It is found that the bending moment response developed in the core projection induced by end rotation was the main cause for such a failure mode, and it is suggested that core projection should be kept within elastic stage under the possible maximum axial load and bending moment response.